2019
DOI: 10.1016/j.trci.2019.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Aiding the discovery of new treatments for dementia by uncovering unknown benefits of existing medications

Abstract: IntroductionThere is a significant need for disease-modifying therapies to treat and prevent dementia, including Alzheimer's disease. Availability of real-world observational information and new analytic techniques to analyze large volumes of data can provide a path to aid drug discovery.MethodsUsing a self-controlled study design, we examined the association between 2181 medications and incidence of dementia across four US insurance claims databases. Medications associated with ≥50% reduction in risk of demen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“… 37 , 38 However, a recent study examining medications associated with a decreased risk of dementia found no protective effects of TNFI therapies when using a self‐controlled cohort design, comparing use of TNFI versus no TNFI use. 39 …”
Section: Discussionmentioning
confidence: 99%
“… 37 , 38 However, a recent study examining medications associated with a decreased risk of dementia found no protective effects of TNFI therapies when using a self‐controlled cohort design, comparing use of TNFI versus no TNFI use. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 illustrates the study design for a single condition outcome. The REWARD framework has been used in previous studies examining treatments associated with the prevention of parkinsonism and Alzheimer’s disease [ 14 , 15 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…We have built upon advances in statistical methodologies and computing power to create the real-world assessment and research of drug performance (REWARD) framework for studying the association between thousands of medications with thousands of outcomes in millions of patients. Prior work leveraging this framework has focused on specific outcomes of interest to identify heretofore unappreciated uses of existing drugs to treat or prevent a specific disease [ 14 , 15 ]. In this study, we have taken the reverse approach, by examining exposure to a single drug, memantine, and measuring its association with all potential outcomes, in order to identify potential indications for new NMDA receptor antagonist therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease) (106,108). Dysregulated SGR in brain disorders like AD implicates a range of SGR-related processes involving molecular targets that could be therapeutically accessible by targeting variant genes, their expressed products or specific enzymes-for example, by using the RT inhibitors that are already approved by the Food and Drug Administration for treating HIV (106,109); post hoc literature analyses support potential benefits of RTs in AD (106,(109)(110)(111).…”
Section: Sgr In Age and Diseasementioning
confidence: 99%